Zrobię :)
[tex]b) \frac{2}{3}-[0.8 * \frac{3}{(-2)^2} - \frac{(-2)^2}{5}] : (-1\frac{1}{2}) = \frac{2}{3}-[\frac{4}{5}*\frac{3}{4}-\frac{4}{5}]:(-\frac{3}{2})=\frac{2}{3}-[\frac{3}{5}-\frac{4}{5}]*(-\frac{2}{3})=\frac{2}{3}-(-\frac{1}{5})*({-\frac{2}{3}})=\frac{2}{3}-\frac{2}{15}=\frac{10}{15}-\frac{2}{15}=\frac{8}{15}[/tex]
[tex]c) (\frac{1}{3}-\frac{1}{2}):(\frac{5}{3}-\frac{5}{4})-(0.25-\frac{3}{8}:0.625)=(\frac{2}{6}-\frac{3}{6}):(\frac{20}{12}-\frac{15}{12})-(\frac{1}{4}-\frac{3}{8}:\frac{5}{8})=-\frac{1}{6}*\frac{12}{5}-(\frac{1}{4}-\frac{3}{5})=-\frac{2}{5}-(\frac{5}{20}-\frac{12}{20})=-\frac{2}{5}+\frac{7}{20}=-\frac{8}{20}+\frac{7}{20}=-\frac{1}{20}[/tex]
[tex]d) ((-\frac{1}{2})^2 - (-\frac{1}{2})^3):((-\frac{2}{3})^2-(-\frac{1}{3})^2)=(\frac{1}{4}+\frac{1}{8}):(\frac{4}{9}-\frac{1}{9})=\frac{3}{8}*\frac{9}{3}=\frac{9}{8}=1\frac{1}{8}[/tex]